Analysis Of Regional Revenue And Expenditure Budget For Kediri Regency During The Covid-19 Pandemic - Anik Kurnia Ningsih (CV Putra Publisher, 2023)
The existence of the Covid-19 pandemic has had an impact on all economic sectors including the financial performance of local governments. Regional financial analysis is a tool that can be used as a benchmark to assess the extent to which local government performance is managing its finances. Regional ability to manage finances is described in the form of APBD which directly or indirectly reflects the ability of local governments to finance the implementation of governmental tasks, development and community social services. The purpose of this study was to determine the financial management performance of the Regional Government of Kediri Regency based on the analysis of financial ratios in the Kediri Regency APBD. This research is a data series research, namely the Realization of APBD data for 2020 to 2022 in Kediri Regency. The analysis used is normative juristic with a descriptive approach case study method. The analysis tools used are tax ratio, per capita tax, regional fiscal space, regional dependency ratio, ratio of personnel expenditure to total regional expenditure, ratio of capital expenditure to total regional expenditure, ratio of capital expenditure to population, ratio of financial aids expenditure to total regional expenditure, idle funds, growth ratio, effectiveness ratio, and efficiency ratio. From the results of the analysis it is known that the majority of APBD performance during the Covid-19 pandemic had fluctuations.